KESALAHAN-KESALAHAN SUAMI DALAM RUMAH TANGGA - Arofik, Slamet (USRATUNA: Jurnal Hukum Keluarga Islam, 2020)
In the husband's household is the head of the household. He can be analogous as a president in a country. In his hand there are a variety of responsibilities in order to create a harmonious, happy, safe and secure family order from the world to the hereafter as mandated by the Qur'an surah al-Tahrim [66] verse 06 and also the Prophet's mandate regarding the ideal husband's criteria as stated in many The hadith. In the household there is also no perfection. Both husband and wife have the potential to make mistakes. However, in general in the sense that it is not casuistic, husband's mistakes are more fatal when compared to mistakes made by wives. Therefore the husband must understand and understand what are the behaviors and actions that can make his mistakes in the household. Husband's mistakes in his escort are neglect of birr al-walidain, slow in handling polemics, doubt and prejudice against his wife, minimal jealousy, looking down on his wife, not having the soul of leadership, eating his wife's wealth in a way, not educating his wife about religion, misery against wives, often denounce and criticize wives, mutually silent and do not want to start, rarely at home, opening the secret "bed", not knowing the wife's new habits, intercourse with menstrual conditions, intercourse with the wife through the rectum, hurriedly dropping divorce.